P-153 Induction of IL-33 by the Gut Microbiota in the Pathogenesis of Intestinal Fibrosis in a Spontaneous Mouse Model of IBD. (March 2016) - De Salvo, Carlo; Mattioli, Benedetta; Cominelli, Fabio; Pizarro, Theresa T.
Abstract : Background: Fibrosis is a prominent feature of the 2 primary forms of IBD, Crohn's disease (CD) and ulcerative colitis (UC), characterized by a chronic and relapsing inflammatory condition of the GI tract. Interleukin (IL)-33, is one of the newest members of the IL-1 family of cytokines, involved in several different inflammatory and autoimmune diseases, including IBD. The goal of this study is to determine the role of the commensal flora in inducing IL-33 and Th2 immune response, and its impact on intestinal fibrosis in an experimental model of IBD, i.e., SAMP1/YitFc (SAMP) mouse strain. Methods: Characterization of IL-33 was performed on specific pathogen-free (SPF)-SAMP with established disease/fibrosis and compared to age-matched SPF-AKR (parental control mice) and germ-free (GF)-SAMP. IL-33 blockade was obtained by treating SPF-SAMP mice with an antibody against its receptor, the ST2. Oral administration of fecal antigen was performed on GF-SAMP mice. RNA expression was measured with rtq-PCR, proteins level by ELISA assay. Immunohistochemistry (IHC) was performed to detect IL-33 in full thickness distal ileal tissue and Masson's trichrome stain was used to detect collagen deposition. Results: IL-33 was significantly increased in SAMP versus AKR ilea and immunolocalized to submucosal macrophages and myofibroblasts, co-localizing with fibrotic lesions, which diminished following anti-ST2 treatment. Also Th2 cytokines and profibrogenic genes levels, particularly TGFβ, were decreased in anti-ST2 treated mice compared to IgG-treated controls. Moreover, IL-33 and Th2 cytokines were markedly decreased in GF-SAMP versus SPF-SAMP, whereas administration of fecal antigens in GF-SAMP mice induced a remarkable increase in IL-33 expression. Conclusions: Together these data show that IL-33 expression/production is highly dependent on the presence of the gut microbiota and may serve as a primary mediator of profibrotic events leading to intestinal fibrosis in IBD.